PEMBERDAYAAN KELOMPOK TANI DI DESA PERANGIAN MENGGUNAKAN PUPUK RAMAH LINGKUNGAN UNTUK MENGHASILKAN SAYURAN BERBASIS ORGANIK - Suharman Suharman; Putriyani S; Suparman Suparman; Josi Josi; Nurafni Syamsul; Niar Niar; Muhammad Burhan (Universitas Muhammadiyah Tapanuli Selatan, 2022)
One of the commodity centers for shallots and other secondary crops such as cabbage, chilies, tomatoes, corn, celery leaves, leeks, etc., is in Warian Village, Baraka District, Enrekang Regency. Farmers in the village of Waria use chemical fertilizers to increase the production of agricultural products. Excessive use of chemical fertilizers has an impact on the decreasing quality of land which has the next effect, namely the use of chemical fertilizers is increasingly uncontrolled. Another problem that arises is the increasing scarcity of subsidized fertilizers while non-subsidized fertilizers circulating in the market are not cheap. Because of these problems, this community service activity is carried out in the form of socialization to provide an understanding of the benefits and impacts of using organic fertilizers, training activities for making organic fertilizers using agricultural waste, and empowerment activities to increase the economic value of agricultural waste. The objectives to be achieved in empowerment activities include: 1) Obtaining a method of making organic fertilizer by utilizing agricultural waste and livestock manure; 2) Developing plant cultivation that uses more organic fertilizers 3) Increasing the economic value of agricultural waste in the form of ready-to-use organic fertilizers. The method of activity is an approach to farmers to grow and increase the motivation of farmer groups. Activities to be carried out: 1) Training and demonstrations on the manufacture of organic fertilizers made from agricultural waste, cow dung and chicken manure using local micro-organisms Tricoderma sp and commercial activators such as EM4-, 2) Making pilot vegetable cultivation using organic fertilizers, 3) Demonstration of making ready-to-package organic fertilizer.